The Effect of using Teaching Maps in changing the Concepts of Physical preparation ofThe Methods of teaching Physical Education - Ibrahim, Mahjoub; Abedulwahab, Nabeel (Journal of Physical Education, 2009)
The study aim to identify the concepts of physical preparation which have been misunderstood for the 4th- year students of the departments of physical education . It also aims to know the effect of maps on changing the concepts of physical preparation for the students. The sample of the study consists of (60) male and female student for the Department of Physical Education at the 4th- stage. The sample is divided into two Groups , one experimental and one control, Each group consists of (30) students. The results of analysis shows that there is difference between the two groups in favors of the experimental group which is trained through using maps in comparison with the control group which is trained according to the conventional method. Using maps of concepts has motivated students to participate actively in the activities during the experiment. The study recommends the use of maps of concepts in teaching all the subjects of the department and in training the students in how to make and design maps . The study also recommends training the teaching staff in how to use maps of concepts in there in service training courses. The fifth chapter (Conclusions Recommendations)